The Authority Of Advocates In Providing Legal Assistance To People Having Problems With The Legal - Ninik Mutiah; Ibnu Subarkah; Subadi; Anik Tri Haryani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: Access to justice remains a significant challenge for many people, particularly those with limited legal knowledge and resources. Despite the existence of regulations that guarantee the role of advocates, gaps between legal norms and practical implementation persist, leading to inequality before the law. The authority of advocates in providing legal assistance is therefore essential to ensure fairness and human rights protection. Purpose/Study Objectives: This article aims to analyze the authority of advocates in providing legal assistance to individuals facing legal problems and to evaluate its role in strengthening access to justice. Design/Methodology/Approach: The study adopts a normative juridical method with a statute and conceptual approach, supported by literature reviews from books, journals, and regulations relevant to the role and authority of advocates. Findings: The findings indicate that the authority of advocates is crucial in safeguarding citizens’ rights, ensuring fair trials, and promoting equality before the law. However, challenges remain, such as limited public awareness, bureaucratic obstacles, and insufficient access for marginalized communities. The strengthening of advocates’ authority, coupled with ethical accountability and legal reform, is essential for improving justice delivery. Paper Type: Research Article.